Effect of ZnO on the Thermal Properties of Tellurite Glass - H. A. A. Sidek; S. Rosmawati; B. Z. Azmi; A. H. Shaari (Advances in Condensed Matter Physics)
Systematic series of binary zinc tellurite glasses in the form (ZnO)x(TeO2) (where x=0 to 0.4 with an interval of 0.05 mole fraction) have been successfully prepared via conventional melt cast-quenching technique. Their density was determined by Archimedes method with acetone as buoyant liquid. The thermal expansion coefficient of each zinc tellurite glasses was measured using L75D1250 dilatometer, while their glass transition temperature (Tg) was determined by the SETARAM Labsys DTA/6 differential thermogravimetric analysis at a heating rate of 20 K min−1. The acoustic Debye temperature and the softening temperature (Ts) were estimated based on the longitudinal (VL) and shear ultrasonic (Vs) wave velocities propagated in each glass sample. For ultrasonic velocity measurement of the glass sample, MATEC MBS 8000 Ultrasonic Data Acquisition System was used. All measurements were taken at 10 MHz frequency and at room temperature. All the thermal properties of such binary tellurite glasses were measured as a function of ZnO composition. The composition dependence was discussed in terms of ZnO modifiers that were expected to change the thermal properties of tellurite glasses. Experimental results show their density, and the thermal expansion coefficient increases as more ZnO content is added to the tellurite glass network, while their glass transition, Debye temperature, and the softening temperature decrease due to a change in the coordination number (CN) of the network forming atoms and the destruction of the network structure brought about by the formation of some nonbridging oxygen (NBO) atoms.